Single‐Site vs. Cluster Catalysis in High Temperature Oxidations. Issue 29 (9th June 2021) - Serna, Pedro; Rodríguez‐Fernández, Aida; Yacob, Sara; Kliewer, Christine; Moliner, Manuel; Corma, Avelino
Abstract: The behavior of single Pt atoms and small Pt clusters was investigated for high‐temperature oxidations. The high stability of these molecular sites in CHA is a key to intrinsic structure–performance descriptions of elemental steps such as O2 dissociation, and subsequent oxidation catalysis. Subtle changes in the atomic structure of Pt are responsible for drastic changes in performance driven by specific gas/metal/support interactions. Whereas single Pt atoms and Pt clusters (> ca. 1 nm) are unable to activate, scramble, and desorb two O2 molecules at moderate T (200 °C), clusters <1 nm do so catalytically, but undergo oxidative fragmentation. Oxidation of alkanes at high T is attributed to stable single Pt atoms, and the C‐H cleavage is inferred to be rate‐determining and less sensitive to changes in metal nuclearity compared to its effect on O2 scrambling. In contrast, when combustion involves CO, catalysis is dominated by metal clusters, not single Pt atoms. Abstract : Metal active sites speciation on Pt‐CHA is discussed for different high‐temperature oxidation reactions, including 16 O2 / 18 O2 isotopic exchange experiments, methane combustion, and CO oxidation. Structure–performance relationships built on subtle changes in the active sites under working conditions are revealed.